Application of Multipoint DC Voltage Control in VSC-MTDC System. (11th July 2013) - Xi, Yang; Qian, Ai; Jiantao, Huang; Yiran, An
Abstract : The voltage-source-converter- (VSC-) based multiterminal VSC-HVDC power transmission system (VSC-MTDC) is an ideal approach to connect wind farm with power grid. Analyzing the characteristics of doubly fed induction generators as well as the basic principle and the control strategy of VSC-MTDC, a multiterminal DC voltage control strategy suitable for wind farm connected with VSC-MTDC is proposed. By use of PSCAD/EMTDC, the proposed control strategy is simulated, and simulation results show that using the proposed control strategy the conversion between constant power control mode and constant DC voltage control mode can be automatically implemented; thus the DC voltage stability control and reliable power output of wind farm can be ensured after the fault-caused outage of converter station controlled by constant DC voltage and under other faults. The simulation result shows that the model can fulfill multiterminal power transmission and fast response control.